The prevalence and risk factors for foot pressure ulcers in ambulatory pediatric patients with spina bifida. Issue 9 (24th April 2021) - Rethlefsen, Susan; Mueske, Nicole; Wren, Tishya; Murgai, Rajan; Bent, Melissa
Abstract: Aim: To determine prevalence, incidence and risk factors for foot pressure ulcers in ambulatory children with spina bifida. Method: Retrospective cohort study of 72 ambulatory children (age range 0–23.9 years) with spina bifida treated at a pediatric tertiary care facility. Data on foot pressure ulcers were recorded and analyzed to determine prevalence, incidence and predictive factors. Results: Foot pressure ulcers occurred in 50/143 limbs (35%) over 10.5 ± 3.5 years. Average incidence was 0.10 foot pressure ulcer incidents per person-year, and prevalence in years with complete follow-up was 8.8%. Prevalence was related to age [higher for ages 11–15 (17%), than ages 0–10 (5%) and 16+ years (7%), p < 0.0001], and varus/valgus foot deformities ( p < 0.001) and brace use (0.32 risk difference, p = 0.01), but not with standing foot position, deformity rigidity, body mass index, spina bifida type, lesion level, ambulatory level or co-morbidities. Most common sites were the heel (21/96, 22%), lateral malleolus (12/96, 13%), and plantar 5 th metatarsal head (11/96, 12%). Conclusion: Foot pressure ulcers occur in nearly 1 out of 10 ambulatory children with spina bifida, most often in pre-teens or young teen-agers with foot deformities, who use braces. This information can help direct skin care education and prevention to those most vulnerable. Implications for Rehabilitation: Foot pressure ulcers occur in children and adolescents with spina bifida, most commonly in those aged 11-15 years, with foot deformities and who use braces. Ulcer development was unrelated to stiffness of foot deformity, body mass index, lesion or functional level, or presence of comorbidities such as Arnold-Chiari malformation, syringomyelia or shunted hydrocephalus. Skin care education and preventative measures should be provided to all patients, but with particular emphasis for those with these risk factors.